Penggunaan Aplikasi Digital Marketing Dalam Upaya Pengembangan Umkm - Zumrotul Fitriyah; Rafael Kelvlin Sofani; Crysanti Chandra Asia; Muhammad Rizki Firmansyah (Pusat Riset dan Inovasi Nasional, 2023)
Micro, Small and Medium Enterprises (MSMEs) are businesses which are run by individuals which refer to productive economic businesses. MSMEs in sales are more effective when using digital marketing. Currently, the development of technology is increasingly advanced, where the technology that is made will be more sophisticated. Marketing currently uses digital media, where previously offline marketing is now using an online marketing system. The use of digital technology-based marketing will give hope to MSMEs to develop. In this case the use of applications in product marketing, where the use of applications can facilitate the marketing of a product. Utilization of digital marketing uses 3 stages, namely conducting surveys and socialization, implementing activities and evaluating and results.